Co‐introduction of a steroid with docetaxel chemotherapy for metastatic castration‐resistant prostate cancer affects PSA flare. (6th April 2016) - Shiota, Masaki; Yokomizo, Akira; Takeuchi, Ario; Kiyoshima, Keijiro; Inokuchi, Junichi; Tatsugami, Katsunori; Shiga, Ken‐ichiro; Koga, Hirofumi; Yamaguchi, Akito; Naito, Seiji; Eto, Masatoshi
Abstract : Objective: To investigate the potential relationship of steroid usage with prostate‐specific antigen (PSA) flare as well as the prognostic impact of PSA flare, which is known to occur in 10–20% of patients with metastatic castration‐resistant prostate cancer during docetaxel chemotherapy. Patients and Methods: This study included 71 patients with metastatic castration‐resistant prostate cancer treated by docetaxel chemotherapy with co‐introduction of a steroid. PSA flare was defined as a transient PSA increase followed by a PSA decrease. Results : PSA flare was recognized in 7.0–23.9% of patients according to the definition used. Intriguingly, men with steroid intake before the initiation of docetaxel chemotherapy experienced significantly fewer PSA flares. The progression‐free survival rate in men with PSA flare was equivalent to that of PSA responders, but significantly better than men with PSA failure. Conclusions: Our results suggest that de novo steroid co‐introduction with docetaxel chemotherapy induces the PSA flare phenomenon. This novel finding may account for the mechanism of PSA flare as well as being valuable for distinguishing PSA elevation attributable to PSA flare from that attributable to PSA failure.